Michelangelo - Stanley, Diane (New York : HarperCollins, 2000)
A biography of the Renaissance sculptor, painter, architect, and poet, well known for his work on the Sistine Chapel in Rome's St. Peter's Cathedral.
Includes bibliographical references (p. [48]).
Wilson's Children.
Wilson's Junior High School.
School Library Journal starred.
5.3
3-6
Keywords: Michelangelo Buonarroti, -- 1475-1564 -- Juvenile literature; Michelangelo Buonarroti, -- 1475-1564.; Michelangelo Buonarroti, -- 1475-1564.; Artists -- Italy -- Biography -- Juvenile literature; Artists; Artists -- Italy -- Biography; Artists; Sculptors; Renaissance -- Italy